2021
DOI: 10.5194/hess-2021-456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xylem water in riparian Willow trees (Salix alba) reveals shallow sources of root water uptake by in situ monitoring of stable water isotopes

Abstract: Abstract. Root water uptake is an important critical zone process, as plants can tap various water sources and transpire these back into the atmosphere. However, knowledge about the spatial and temporal dynamics of root water uptake and associated water sources at both high temporal resolution (e.g. daily) and over longer time periods (e.g. seasonal) is still limited. We used cavity ring-down spectroscopy (CRDS) for continuous in situ monitoring of stable water isotopes in soil and xylem water for two riparian… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…Additionally, a previous greenhouse experiment that also investigated the cryogenic extraction impact on xylem water using S. viminalis cuttings (the same species used in this experiment) showed no bias for δ 2 H and only a small but consistent enrichment in δ 18 O above soil water (Newberry et al, 2017). In situ monitoring of xylem (e.g., Landgraf et al, 2021; Marshall et al, 2020; Volkmann, Kühnhammer, et al, 2016) and phloem water isotopic composition could likely improve uncertainties related to extraction method and would provide higher temporal‐resolution measurements. However, in situ monitoring of phloem (i.e., inner bark) has not been tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous greenhouse experiment that also investigated the cryogenic extraction impact on xylem water using S. viminalis cuttings (the same species used in this experiment) showed no bias for δ 2 H and only a small but consistent enrichment in δ 18 O above soil water (Newberry et al, 2017). In situ monitoring of xylem (e.g., Landgraf et al, 2021; Marshall et al, 2020; Volkmann, Kühnhammer, et al, 2016) and phloem water isotopic composition could likely improve uncertainties related to extraction method and would provide higher temporal‐resolution measurements. However, in situ monitoring of phloem (i.e., inner bark) has not been tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…A lake water extraction facility (using bank filtration) is situated immediately north of the IGB site, and groundwater is ∼ 2.2 m below the ground surface with limited annual variability (< 0.1 m). A previous isotope-based study at the site has excluded groundwater and the nearby stream water as likely sources of water to the trees (Landgraf et al, 2021).…”
Section: Study Sitementioning
confidence: 99%
“…Willows are a riparian species which is well adapted to moderate and high moisture typical of riparian areas or those with high groundwater levels (Isebrands and Richardson, 2014). Additional site selection criteria are provided in Landgraf et al (2021). The willows have a similar age of ∼ 15 years with the willow in the north (Willow 1, Fig.…”
Section: Soils and Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotope measurements of the transpiration flux become more widely available due to lower costs and new technologies (Marshall et al, 2020;Volkmann et al, 2016), which allows sub-daily to daily xylem isotope analysis. However, such in-situ measurements have shown that xylem water isotope variation is by far less responsive than stream water isotopes (Gessler et al, 2021;Landgraf et al, 2021;Seeger and Weiler, 2021). Further, recent simulations with the EcH2O-iso model by 5 Knighton et al (2020) indicated that mixing of water in plants could conceivably dampen rootuptake signals, undermining the insights that could be gained by high frequently xylem sampling.…”
Section: Plant Water Isotopes Indicate That Trees Use Older Water Tha...mentioning
confidence: 99%